1658 Acute Kidney Injury after Heart Surgery in Children. (October 2012) - Halal, MGDS El; Carvalho, PRA; Bohrer, CV; Pearson, AP
Abstract : Background and Aims: Acute kidney injury (AKI) has been associated to adverse outcomes in children after heart surgery, but previous studies have used several different definitions of AKI. After publication of the pediatric RIFLE (pRIFLE) criteria, it has been widely used as a definition for AKI in children. This study aims to investigate association between occurrence of AKI according to pRIFLE criteria and adverse outcomes in children after heart surgery. Methods: Children submitted to open heart surgery in a hospital in Brazil were followed from arrival until death or discharge from the Pediatric Intensive care Unit (PICU). The exposition variable was occurrence of AKI according to pRIFLE criteria, which divides AKI in three categories: R-Risk, I-Injury, F-Failure, according to changes in urine output or the estimated glomerular filtration rate. The outcomes studied were death, length of mechanical ventilation (MV) and length of PICU stay. Results: Eighty five children were studied. Forty seven (55.3%) did not have AKI during PICU stay, while 22 (25.9%), 7 (8.2%) and 9 (10.6%) were classified as R, I and F, respectively. Comparing to children who did not develop AKI, the relative risk for death was 1.07 (0.09–12.48), 16.87 (2.14–132.50) and 11.25 (1.55–81.61) in the R, I and F group, respectively (p = 0, 001). Lengths of MV and of PICU stay were significantly higher in those with any degree of AKI. Conclusions: Occurrence of AKI according to pRIFLE criteria is associated to adverse outcomes in children after open heart surgery.